Survival trends in young patients with Waldenström macroglobulinemia: Over five decades of experience. Issue 3 (1st January 2023) - Chohan, Karan L.; Paludo, Jonas; Vallumsetla, Nishanth; Larson, Dirk; King, Rebecca L.; He, Rong; Gonsalves, Wilson; Inwards, David; Witzig, Thomas E.; Swaika, Abhisek; Jain, Tania; Leung, Nelson; et al.
Abstract: Waldenström macroglobulinemia (WM) is a rare, indolent lymphoma, that predominately affects the elderly. We report the outcomes of young WM patients, evaluated over five decades, compared to their older counterparts, matched for the time of diagnosis. Between January 1, 1960 and October 31, 2013, 140 (11.8%) WM patients were ≤50 years of age at diagnosis in our database, and their estimated 10‐year overall survival (OS) was 74%, with death attributable to WM in a higher proportion of patients compared to their older (≥65 years) counterparts (91% vs. 58%, p = .0001). Young patients were grouped into three cohorts based on the timing of the initiation of therapy: Group 1 (1960–1977, n = 12), Group 2 (1978–1995, n = 48), and Group 3 (1996–2013, n = 74). Among young patients, there was no disease‐specific survival (DSS) difference across the three periods, [median DSS at 13 years (95% CI 5–23), 16 years (95% CI 14–22), and 15 years (95% CI 10‐NR; p = .41), respectively]. However, DSS for the older cohort incrementally improved (Group 1, median 5.2 years, Group 2: 9.6 years, Group 3: 12 years; p = .05) over these periods. The estimated average years‐of‐life lost for the young cohort was 11.2 years from diagnosis, based on the expected survival for a normal age‐ and sex‐matched population. Despite a protracted disease course, nearly all young patients succumb to their disease. In contrast to the improved survival of the elderly patient population, the evolving treatment strategies in WM have not impacted the outcome of young patients; however, the impact of Bruton tyrosine kinase inhibitors on this unique patient population remains to be determined.